Anaesthesia Department Preparedness and Response for the COVID-19 Outbreak in Portugal: A Perspective from CUF Porto Hospital: Preparação e Resposta do Departamento de Anestesia para o Surto COVID-19 em Portugal: Uma Perspetiva do Hospital CUF Porto - Figueiredo, Manuel; Leão, Ana; Moreno, Carlos; Fernandes, Marcelo; Hernandez, Angel; Correia, José Manuel; Gouveia, Marcos; Ramos, Paulo; Fonseca, Sara; Faria, Tiago; Santos, Pedro; Oliveira, Raquel; et al. (Gazeta Médica, 2020)
A global health emergency has been declared by the World Health Organization (WHO) as the SARS-CoV-2 outbreak spread across the world. Patients infected with SARS-CoV-2 are at risk for developing respiratory failure and requiring admission to critical care units. While providing optimal treatment for these patients, careful execution of infection control measures is necessary to prevent nosocomial transmission to other patients and to health workers providing care.1 In the operating room, these preparations involve multiple stakeholders and can present a significant challenge. Here we described the measures for the outbreak adopted by the anesthesia department of a private tertiary care level hospital in Porto. These include engineering controls such as: identification and preparation of an isolation operating rooms, administrative measures such as: modification of workflow and processes, introduction of personal protective equipment, and formulation of clinical guidelines for anaesthetic management. We discuss how the hierarchy of controls should be a framework to plan, the necessary measures during each phase of a pandemic, and review the evidence of the procedures taken. [...]